2018
DOI: 10.1093/cid/ciy819
|View full text |Cite
|
Sign up to set email alerts
|

Measles Outbreak at a Privately Operated Detention Facility: Arizona, 2016

Abstract: Background.-We describe a measles outbreak and control measures implemented at a privately operated detention facility housing US Immigration and Customs Enforcement detainees in 2016. Methods.-Case-patients reported fever and rash and were either laboratory-confirmed or had an epidemiological link to a laboratory-confirmed case-patient. Immunoglobulin G (IgG) avidity and plaque reduction neutralization tests distinguished between primary acute and reinfection casepatients. Measles-specific IgG was measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…52 All described outbreaks occurred in adult custodial facilities, with the exception of one which took place in a youth custody facility. 60 One outbreak was observed in a privately operated immigration detention centre, 66 but the remainder were…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…52 All described outbreaks occurred in adult custodial facilities, with the exception of one which took place in a youth custody facility. 60 One outbreak was observed in a privately operated immigration detention centre, 66 but the remainder were…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…45 56 59 66 One study identified potential exposure in the community through staff index cases at multiple locations (eg, food shops, healthcare facilities, petrol stations, etc). 66 Letters were sent to released people with known contacts to inform them of possible exposure and the need for screening. 56 59 Individual contact tracing can be unfeasible given the potentially large numbers.…”
Section: Contact Tracingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also unknown whether these outbreaks were due to low vaccination rates or waning immunity, as immunization records are usually unavailable for detainees in ICE facilities. 53 Limited published studies exist on disease outbreaks within US detention centres, however, one study which examined a 2016 measles outbreak in an Arizona detention centre determined that a high proportion of detainees had received at least one dose of MMR. 53 Additionally, most of the detainees in US detention centres originate from the Americas, where median vaccination coverage has been >90% since the 1990s.…”
Section: Discussionmentioning
confidence: 99%